Home grounds - Maelzer, Amelia Augusta (My University, 1902)
Introduction: The subject of home grounds is a question of vital importance to this and every other country. What a vast difference it would make in the appearance of our Kansas plains to have them dotted with elm and pine groves, orchards, and artistically arranged into home grounds – God has given us the material, why not make use of it. Home may be defined in many different ways but the things it stands for are harmony, order, neatness and contentment. It is the center for our affections and the throne on which love reigns supreme. Whatever may be contemplated there should be a definite plan at the outset. Haphazard efforts do not produce the effects of beauty, repose, contrast, harmony, variety and unity produced by thorough and thoughtful plan. We can also say that home should reflect the culture, refinement and order of its inhabitants and that in planning home grounds special attention should be given to the inner consciousness of the home. That this “atmosphere” should be made manifest demands a plan. The home should first be established then the development of the grounds into picturesqueness and comfort will follow in natural sequence and will be a source of great pleasure to the one who attempts this good work. Sometimes many years are required in carrying out to perfection a complicated plan, but the grandeur, beauty and usefulness as the result of such faithful and untiring effort is inestimable in the eyes of the home and commonwealth.
Citation: Maelzer, Amelia Augusta. Home grounds. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Homes; Grounds; Horticulture; Gardening; Landscaping; Theses